Effect of the Sodium Polyacrylate on the Magnetite Nanoparticles Produced by Green Chemistry Routes: Applicability in Forward Osmosis - Juan Zufía-Rivas; Puerto Morales; Sabino Veintemillas-Verdaguer (Nanomaterials, 2018)
Aqueous dispersions of magnetic nanocomposites have been proposed as draw electrolytes in forward osmosis. One possible approach for the production of nanocomposites based on magnetite nanoparticles and sodium polyacrylate is the synthesis of the magnetic iron oxide by coprecipitation or oxidative precipitation in the presence of an excess of the polymer. In this work, we explored the effect of the polymer proportion on the nanomaterials produced by these procedures. The materials obtained were compared with those obtained by the coating of magnetite nanocrystals produced beforehand with the same polymer. The samples were characterized by chemical analysis, photon correlation spectroscopy, thermogravimetry, X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and magnetometry. The general trend observed is that the polymers heavily modify the texture of the magnetic material during the synthesis, with a drastic reduction of the particle size and magnetic response. The polycrystalline texture that is generated permits the incorporation of the polymer both on the external surface and in the intergranular space. The aqueous dispersions of the nanocomposites were highly stable, with a hydrodynamic size that was roughly independent of the polymer/magnetite ratio. Such dispersions show an osmotic pressure that is proportional to the concentration of the polymer. Interestingly, the proportionality constant was similar to that of the free polymer only in the case of the samples prepared by oxidative precipitation, being lower in the case of the samples prepared by coprecipitation. Finally, the possibilities of using these materials as draw electrolytes in forward osmosis will be briefly discussed.